Atlas of human anatomy. - Netter, Frank H. (Frank Henry), 1906-1991 (Philadelphia, Pennsylvania : Saunders, 2006)
Netter's Atlas of Human Anatomy is the most loved and best selling anatomy atlas in the English language. In over 540 beautifully colored and easily understood illustrations, it teaches the complete human body with unsurpassed clarity and accuracy. This new edition features 57 revised, 200 relabeled and 17 wholly new plates, drawn fully in the tradition of Frank Netter, and includes more imaging and clinical images than ever before. Table of contents Section 1 - Head and Neck Section 2 - Back and Spinal Cord Section 3 - Thorax Section 4 - Abdomen Section 5 - Pelvis and Perineum Section 6 - Upper Limb Section 7 - Lower Limb Section 8 - Cross-Sectional Anatomy
Keywords: Anatomie